Association of cd44⁺cd24⁻/low with markers of aggressiveness and plasticity of cell lines and tumors of patients with breast cancer - Chekhun, V.F.; Lukianova, N.Y.; Chekhun, S.V.; Bezdieniezhnykh, N.O.; Zadvorniy, T.V.; Borikun, T.V.; Polishchuk, L.Z.; Klyusov, O.M. (Experimental Oncology, 2017)
Aim: To search for additional molecular-biological markers of cancer stem cell (CSC) involved in the development of intra-tumor heterogeneity for the detection of features of the breast cancer (BC) pathogenesis. Materialts and Methods: Expression of estrogen receptors (ER), progesterone receptors (PR), Her2/neu, E- and N-cadherin, CD24, CD44, Bcl-2, Bax, Slug, P-gp, glutathioneS-transferase (GST) and metallothionein in cell lines was determined by the immunocytochemical method. Expression of ER, PR, Her2/neu, CD24 and CD44 in the surgical material of BC patients were determined by the immunohistochemical method. The levels of the miRNA were determined using real-time polymerase chain reaction. Results: Cells of high-grade malignancy (HGM), MDA-MB-231 and MDA-MB-468 are characterized by high expression of stem cell markers compared to the cells of low-grade malignancy (LGM), T47D and MCF-7: CD44 levels in T47D and MCF-7 cells were in range of 72–79 points, which is significantly lower than in HGM cells (p < 0.05). Also, HGM cells with the properties of CSC were characterized by high expression of antiapoptotic proteins, the transcription factor Slug, and low levels of proapoptotic protein Bax (p < 0.05) compared to LGM cells. In cells with CSC characteristics an increased expression of transferrin and its receptor, ferritin, fentorin and hepcidin was revealed indicating activation of the endogenous iron metabolism. The characteristic feature of HGM cells with CSC phenotype were the increased levels of oncogenic miR-221, -155 and -10b by 60%, 92% and 78%, respectively, and decreased levels of oncosuppressive miR-29b, -34a and -200b by 8.4 ± 0.3, 4.6 ± 0.2, and 3.4 ± 0.6 times compared to MCF-7 line cells. It has been established that the development of resistance to cytostatics is accompanied by increased aggressiveness of tumor cells, loss of expression of hormonal receptors and acquiring of stem phenotype. In particular, increased expression of P-gp was observed in BC cells during the development of resistance to doxorubicin, of GST during the development of resistance to cisplatin along with increased CD44 expression (p < 0.05). We have revealed the relation between the presence of cells with the CSC phenotype (CD44⁺CD24⁻/low ) and clinical and pathological characteristics of BC patients, their survival and BC sensitivity to neoadjuvant therapy (p > 0.05). Conclusions: The dependence between the expression of CSC markers and the degree of malignancy of tumor cells, development of resistance to cytostatics in vitro was established as well as the predictive value of the detection of the CSC for the individual prognosis of the BC course and sensitivity of the tumors to the treatment.